Rebound tonometry compared with goldmann applanation tonometry in patients with corneal pathology - a reliability study - Lamprecht, Johann Streicher (My University, 2016)
Purpose: To compare the reliability of rebound tonometry (RT) with that of Goldmann applanation tonometry (GAT) in patients with corneal scars. Methods: Three measurements were taken with each instrument. Instruments were compared by determining the differences between repeat measurements, by using a nonparametric ANOVA on repeat measurements and by calculating the coefficient of repeatability (CR). A control group with normal corneas were examined to establish baseline correlation, repeatability and observer proficiency. Results: 61 eyes of 48 patients were included in the group with scarred corneas. The CR of RT was 2.667. The CR of GAT was 4.819. RT was more reliable than GAT in patients with corneal scars. The correlation coefficient of RT with GAT was 0.8959. Conclusion: RT correlated well with GAT in both scarred and control subjects. RT was more reliable than GAT in patients with corneal scars. GAT was more reliable than RT in control patients.
A research report submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Science in Medicine in the branch of Ophthalmology Johannesburg, November 2016